1994
DOI: 10.1007/bf00334329
|View full text |Cite
|
Sign up to set email alerts
|

Chicken soup revisited: Calcium content of soup increases with duration of cooking

Abstract: Because low dietary calcium intake may accelerate bone loss, patients often are advised to increase their dietary intake of calcium. However, some patients may be unable to tolerate good calcium sources such as dairy products. We postulated that the calcium content of soups and stews could be increased by prolonged cooking with a beef bone. Three experiments were done to prove this theory: (1) a bone soup made with a beef bone and distilled water, cooked for 24 hours; (2) a bone-vegetable soup cooked the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Animal bones contain minerals and so simmering them is generally believed to produce a broth that also contains minerals. Studies have demonstrated that calcium and magnesium levels in broth are generally related to cooking time [ 7 ], but little is known about the extraction of other elements, including toxic metals, in broths.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Animal bones contain minerals and so simmering them is generally believed to produce a broth that also contains minerals. Studies have demonstrated that calcium and magnesium levels in broth are generally related to cooking time [ 7 ], but little is known about the extraction of other elements, including toxic metals, in broths.…”
Section: Resultsmentioning
confidence: 99%
“…However, findings have been inconsistent. For example, the calcium concentration in a soup that is made of cow vertebra and various vegetables (simmered for 24 h, pH = 4.48) was found to be ~26 times that in a soup without vegetables (pH = 7.06) [ 7 ]. Conversely, lowering the pH of a soup that was made from chicken wings (simmered for 2–6 h) from ~7.0 to ~5.7 by adding vinegar caused a small increase, by a factor of 1.4, in calcium concentration [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to its cost-effectiveness and short raising term, chicken meat not only has a high economic benefit but also is in high global consumer demand. Chicken meat also has some health benefits with lower fat and cholesterol contents but higher protein content than red meats (Jaturasitha et al, 2008; Rosen et al, 1994). In Korea, chicken meat is cooked with various methods such as roasted, as a steamed dish, and boiled.…”
Section: Introductionmentioning
confidence: 99%